Indicator system to measure the qualities of urban space affecting urban safety and coexistence - Nebot-Gómez-de-Salazar, Nuria; Cornax-Martín, Marta; Chamizo-Nieto, Francisco José; Rosa-Jiménez, Carlos; Becerra-Muñoz, José (My University, 2020)
Urban space design directly influences its own safety. Sometimes this security is given by urban furniture, lighting or urban facilities, among other aspects. This paper presents a methodology based on the development of a system of indicators that provides the opportunity to assess what qualities of urban space influence street safety. It is important to know what aspects of public space make the citizen consider it a safe place and at the same time, to contrast these data with scientific documents. The first results are shown after applying this methodology to the case study of the city of Malaga, and specifically, to a sample of streets selected based on objective criteria crime rate. For research and obtaining indicators, digital surveys have been carried out on a group of 300 people, using Google Forms and social networks. Likewise, to obtain samples of the streets with the highest and lowest crime rates, registration data has been geolocated by the tolls of the Geographic Information Systems (GIS). The main contribution of this document is focused on defining indicators to characterize and quantify the safety in the streets of the urban public space. These are contrasted with objective data and records of insecurity and crime, and can be applicable to any street in any city. Finally, through these indicators, it is intended to know what are the parameters that influence urban safety for future designs of public spaces, or their renovation, achieving in the future, the existence of streets with a higher level of safety.
Preprint de los autores enviado a: IOP Conference Series: Materials Science and Engineering. DOI:10.1088/issn.1757-899x
Keywords: Orden público; Espacios públicos; Vida urbana; Calidad de vida; Indicadores sociales; Delincuencia; Urban safety; Qualities of Urban Space; System of indicators; Citizen surveys; Crime maps